Social media and its role in spreading the sports culture of Algerian football Tamimi High School in M’sila"-Aghlab Al-"a field study at Ibrahim bin Alhavestudents - boussag, fatiha; Sedrati, Habib; boussag, asm (sports creativity, 2025)
The world has recently witnessed several social communication changes in all fields especially with the current technological developments, including social networks as the most important technology for spreading the sports culture of football, which is the most popular sport in the world. We will highlight in our study the real role that these media play among the schooled adolescents, and we have chosen the descriptive analytical approach that is appropriate for the study community consisting of students of the final secondary stage in its various specializations, estimated at 263 pupils, while the sample is part of it and was estimated by 23 pupils. We used the questionnaire as a study tool through which we reached the most important results: "Social media networks have a positive and important role in disseminating the sports culture of Algerian football to schoolchildren."